Standardized Assessments: Six Critical Reflections - Barrenechea, Ignacio (Education Policy Analysis Archives, 2010)
This paper presents a review of the literature analyzing six key limitations of standardized evaluations. The six criticisms are the following: the tension that exists between the concept of multiple intelligences and the standardized evaluations, the disregard of components of the real curriculum - which is not necessarily exhausted in the prescribed curriculum, the risks of teaching to the test, the incentives that are generated to cheat or inflate the results of the tests, the lack of consideration of the economic differences of the pupils who are evaluated, and, finally, the limitations of the results of standardized evaluations as predictors of the labour success of the students. This paper concludes that when this type of evaluation is used as the only basis of educational decisions, the costs outweigh the benefits.